Evolving Ownership Structures, CEO Tenure, and Their Impact on Company Value in Indonesia's Digital Economy - Rina Sulistyowati; Noorlailie Soewarno (AFRE (Accounting and Financial Review), 2025)
This study examines the effect of the relationship between ownership structure (institutional and managerial ownership) and company value mediated by CEO tenure in Indonesia. Sourced from the IDX (https://www.idx.co.id/), the data used are archive, or secondary, records. From 2019 to 2023, 91 service, trade, and investment firms were included in the sample that the researchers used. This investigation employs a quantitative methodology. Archival data, namely secondary data acquired from the IDX (https://www.idx.co.id), are used in this study. This study uses a sample of 154 financial statements from companies listed on the IDX between 2019 and 2023. These companies were listed on the IDX. Institutional ownership is unrelated to firm value, according to the test findings, however managerial ownership is inversely related. There is a positive correlation between CEO duration and company valuation and a negative correlation between CEO term and management ownership, according to the data. Managerial and institutional ownership of a company's value are not moderated by the length of time a chief executive officer is in office JEL Classification: G32, M14DOI: https://doi.org/10.26905/afr.v8i1.14448